Effect of temperature on life history and population growth parameters of Planococcus citri (Homoptera, Pseudococcidae) on coleus [Solenostemon scutellarioides (L.) Codd.] - Goldasteh Shila; Talebi Asghar Ali; Fathipour Yaghoub; Ostovan Hadi; Zamani Abbasali; Shoushtari Vafaei Reza (Archives of Biological Sciences, 2009)
The development, life history, reproduction, and population growth parameters of Planococcus citri Risso on coleus [Solenostemon scutellarioides (L.) Codd.] were studied at various temperatures ranging from 10 to 37ºC, 70±10% RH, and photoperiod length of 16: 8 h (L: D). Females and males successfully developed into adults at from 15 to 32ºC and 18 to 32ºC, respectively. All first instars died at 10, 12, and 37ºC. Lower temperatures (10, 12, and 15ºC) caused higher egg mortality than did higher temperatures (32, 35, and 37ºC). At all temperatures (except 15ºC), the highest percentage of nymphal mortality was observed in the first instar. The sex ratio was female-biased between 15 and 30ºC, but there was a slightly higher number of males at 32ºC. The highest adult longevities of females and males were obtained at 18 and 25°C, respectively. The pre-oviposition, oviposition, and post-oviposition periods were significantly different at various temperatures. The highest fecundity was observed at 23ºC. The shortest and longest oviposition periods occurred at 32 and 18ºC, respectively. Maximum values of the intrinsic rate of natural increase (rm), net reproduction rate (R0), and finite rate of increase (λ) and the shortest mean generation time (T) and doubling time (DT) were obtained at 25ºC. Our findings showed citrus mealybug performances to be highly affected by temperature.